Partnership mapping “Li-chăn – Livestock-led interventions towards equitable livelihoods and improved environment in the North-West Highlands of Vietnam” - Hu Suk Lee; Huyen, Le Thi Thanh; Mai Thanh Tu; Otieno, Mary Atieno; Peters, Michael; Hung Nguyen-Viet; Thinh, Nguyen; Teufel, Nils; Douxchamps, Sabine (CGIAR Research Program on Livestock, 2020)
Effective stakeholder engagement creates positive relationships with stakeholders through communication and the appropriate management of their expectations and agreed objectives (Altshul, 2020). In order to plan for effective stakeholder engagement for the Livestock CRP Vietnam project, we carried out a partnership mapping exercise at national and regional levels. This exercise was carried out in three steps, with two online sessions and one face-to-face meeting, the latter including the in-country team only. The exercise included three steps: (1) to list partners, (2) to position them on power vs. interest diagram (according to our current perception), and (3) to identify and prioritize concrete actions for engagement.